AlN film SAW resonator integrated with metal structure. Issue 5 (1st March 2015) - Shu, Lin; Jiang, Jianying; Peng, Bin; Wang, Yu; Liu, Xingzhao
Abstract : A novel surface acoustic wave (SAW) resonator integrated on a metal substrate is presented. The devices were fabricated on the aluminium nitride (AlN) thin films deposited by mid‐frequency magnetron sputtering on polished TC4 titanium alloy substrates. Using a two‐step growth method, AlN film with a full‐width at half‐maximum of 4.1° had been prepared. The AlN film SAW resonator shows a resonance frequency of 129 MHz and an electromechanical coupling coefficient of 0.28%. The measurement results agree well with the simulation results. This integrated SAW resonator can be used as a good strain sensor in metal structure health monitoring.